Preparation, characterization, and in vitro antibacterial activity of Cu(II)-pyrazinamide complexes, - Galuh Wahyu Karti'a; Danar Purwonugroho; Arie Srihardyastutie; Yuniar Ponco Prananto (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Transition metal complexes, including copper(II) complexes, are being investigated as potential next-generation antibacterial agents. This study aims to prepare several Cu(II)-pyrazinamide (Cu(II)-pza) complexes using Cu(II) salts (acetate, chloride, nitrate, sulphate) through a direct mixing technique. Different Cu(II) salts are anticipated to yield distinct complexes, resulting in varied antibacterial properties. The Cu(II)-pza complexes were characterized using melting point analysis, infrared spectroscopy, and powder X-ray diffraction (XRD). Melting point analysis provides insights into the physical properties of the complexes. Infrared spectroscopy identifies functional groups and predicts chemical bonds within the complexes. Powder XRD analyzes the characteristic diffraction patterns of the complexes. Experimental data reveal that the infrared spectra of all Cu(II)-pza complexes exhibit typical absorption bands of the pyrazinamide ligand (N-H, C=O, C-N, and C=N). Powder XRD analysis shows different diffraction patterns for each complex, indicating the formation of different compounds due to variations in anion and metal-ligand interactions, with the sulphate complex matching a previously reported complex. Melting point tests indicate the decomposition of the complexes within the range of 215–225 °C, except for the acetate complex, which decomposes at 275 °C. The antibacterial activities of these complexes against S. aureus and E. coli were examined in vitro based on inhibition zone diameter and MIC value. The sulphate, nitrate, and chloride complexes exhibit MIC values of 1,000 ppm and MBC values of 6,000 ppm, demonstrating better antibacterial activity against S. aureus than E. coli. These findings suggest the potential of Cu(II)-pza complexes as antibacterial agents. Further studies, such as crystal structure determination, are necessary to explore the possible mechanisms of antibacterial activity.[1]      N. C. Handayani, A. Kusuma, R. Purwanto, R. E. Prasetya, and A. Budiman, “Pengembangan Agen Potensi Pengembangan Agen Antibakteri dari Senyawa Kompleks Logam Transisi di Indonesia,” The Indonesian Green Technology Journal, vol. 10, no. 1, pp. 9-20, 2021.[2]      R. S. Hellberg and E. Chu, “Effects of climate change on the persistence and dispersal of foodborne bacterial pathogens in the outdoor environment: A review,” Crit. Rev. Microbiol., vol. 42, no. 4, pp. 548–572, 2016. doi: 10.3109/1040841X.2014.967385.[3]      T. Li, Y. Wang, X. Zhang, J. Chen, and L. Sun, “Bacterial resistance to antibacterial agents: Mechanisms, control strategies, and implications for global health,” Sci. Total Environ., vol. 860, p. 160148, 2023. doi: 10.1016/j.scitotenv.2022.160148.[4]      N. A. Church and J. L. McKillip, “Antibiotic resistance crisis: challenges and imperatives,” Biologia (Bratisl)., vol. 76, no. 5, pp. 1535–1550, 2021. doi: 10.2478/s11756-021-00707-5.[5]      World Health Organization, "Global Action Plan for antimicrobial resistance,” vol. 105, no. 5, p. 70780, 2015. [Online]. Available: https://www.who.int/publications/i/item/9789241509763.[6]        World Health Organization, "Antibacterial agents in clinical development: an analysis of the antibacterial clinical development," 2019. [Online]. Available: https://www.who.int/publications/i/item/9789240000193.[7]      M. Rizzotto, “Metal Complexes as Antimicrobial Agents,” A Search Antibact. Agents, vol. 10, p. 45651, 2012.[8]      S. N. Sovari and F. Zobi, “Recent Studies on the Antimicrobial Activity of Transition Metal Complexes of Groups 6–12,” Chem., vol. 2, no. 2, pp. 418–452, 2020. doi: 10.3390/chemistry2020025.[9]      M. Claudel, C. Ragonnaud, S. Yousfi, A. Choisy, and R. Gaertner, “New Antimicrobial Strategies Based on Metal Complexes,” Chemistry, vol. 2, no. 4, pp. 849–899, 2020. doi: 10.3390/chemistry2040067.[10]    G. Borthagaray, L. Quintana, F. Brocal, and L. A. Rodríguez, “Infectious Diseases and Epidemiology Essential Transition Metal Ion Complexation as a Strategy to Improve the Antimicrobial Activity of Organic Drugs,” J. Infect. Dis. Epidemiol., vol. 2, no. 2, p. 14, 2016.[11] S. Mittapally, R. Taranum, and S. Parveen, “Metal ions as antibacterial agents,” Journal of Drug Delivery and Therapeutics, vol. 8, pp. 411–419, 2018. doi: 10.22270/jddt.v8i6.2018.[12]    J. Ara Shampa, “Physiochemical and Antibacterial Activity Investigation on Noble Schiff Base Cu(II) Complex,” Am. J. Heterocycl. Chem., vol. 3, no. 4, p. 37, 2017.[13] A. E. Ali, M. El-Ghamry, M. H. Saker, and A. K. Hussein, “Spectral, thermal studies and biological activity of pyrazinamide complexes,” Heliyon, vol. 5, no. 11, p. e02912, 2019. doi: 10.1016/j.heliyon.2019.e02912.[14] Q. C. Burandt, B. L. Knierim, S. Sundström, and F. Jacquet, “Further Limitations of Synthetic Fungicide Use and Expansion of Organic Agriculture in Europe Will Increase the Environmental and Health Risks of Chemical Crop Protection Caused by Copper-Containing Fungicides,” Environ. Toxicol. Chem., vol. 43, no. 1, pp. 19–30, 2024. doi: 10.1002/etc.4995.[15]    M. Vincent, L. Duval, R. Hartemann, J. Noury, and P. Perrin, “Antimicrobial applications of copper,” Int. J. Hyg. Environ. Health, vol. 219, no. 7, pp. 585–591, 2016. doi: 10.1016/j.ijheh.2016.07.003.[16]    M. S. Khan, R. Farooq, M. A. Baig, and H. Shahid, “Computational investigation of pyrazinamide drugs and its transition metal complexes using a DFT approach,” J. Comput. Chem., vol. 45, no. 10, pp. 622–632, 2024. doi: 10.1002/jcc.26563.[17]    E. A. Lamont and N. A. Dillon, “The Bewildering Antitubercular Action of Pyrazinamide,” Microbiology and Molecular Biology Reviews, vol. 84, no. 2, pp. 1–15, 2020. doi: 10.1128/MMBR.00034-19.[18]    N. Raman and R. Jeyamurugan, “Synthesis, characterization, and DNA interaction of mononuclear copper(II) and zinc(II) complexes having a hard-soft NS donor ligand,” J. Coord. Chem., vol. 62, no. 14, pp. 2375–2387, 2009. doi: 10.1080/00958970902932390.[19]    M. M. Khunur and Y. P. Prananto, “Structural analysis of polymeric copper(ii)-pyrazinamide complexes prepared from two different copper(II) salts,” IOP Conf. Ser. Mater. Sci. Eng., vol. 546, no. 6, 2019. doi: 10.1088/1757-899X/546/6/062015.[20]    M. Ahmed, S. H. Naz, M. H. Siddiqui, M. Tahir, and A. S. Farooqi, “Synthesis, characterization and anticancer activity of isonicotinylhydrazide metal complexes,” J. Chem. Soc. Pakistan, vol. 41, no. 1, pp. 113–121, 2019. [Online]. Available: https://jcsp.org.pk/issueDetail.aspx?aid=90.[21]    A. H. Rafika, M. H. Tarafder, K. Mahmood, and S. I. A. Razak, “Effect of drying temperature and drying time on the crystallinity degree of Zn(II)-tartrate complex,” Kuwait J. Sci., vol. 50, no. 4, pp. 596–601, 2023. doi: 10.48129/kjs.v50i4.11354.[22]    S. Tsuzuki, T. Hayashi, K. Muranaka, M. Kamata, T. Iwasaki, and K. Nishimura, “National trend of blood-stream infection attributable deaths caused by Staphylococcus aureus and Escherichia coli in Japan,” J. Infect. Chemother., vol. 26, no. 4, pp. 367–371, 2020. doi: 10.1016/j.jiac.2019.10.014.[23]    A. S. Coia, G. Müller, F. Körner, and H. W. Lang, “Exploring the Role of Transition Metal Complexes in Artistic Coloration through a Bottom-Up Scientific Approach,” J. Cult. Herit., 2024. doi: 10.1016/j.culher.2023.05.004.[24]    M. Manimohan, S. Karthikeyan, M. Ponnuswamy, and M. S. Suriyanarayanan, “Biologically active Co (II), Cu (II), Zn (II) centered water soluble novel isoniazid grafted O-carboxymethyl chitosan Schiff base ligand metal complexes: Synthesis, spectral characterisation, and DNA nuclease activity,” International Journal of Biological Macromolecules, vol. 163, pp. 801-816, 2020. doi: 10.1016/j.ijbiomac.2020.06.118.[25]    W. H. Turner, "Optical Absorption Spectra of Iron in The Rock-Forming Silicates: a Discussion," American Mineralogist: Journal of Earth and Planetary Materials, vol. 52, no. 3-4, pp. 553-555, 1967. doi: 10.2138/am-1967-3-428.[26] Y. Chen, Z. Lu, and X. Zhang, “Applications of Micro-Fourier Transform Infrared Spectroscopy (FTIR) in the Geological Sciences — A Review,” Appl. Spectrosc. Rev., vol. 50, no. 4, pp. 30223–30250, 2015. doi: 10.1080/05704928.2015.1115401.[27]    M. Ali, S. G. Tushar, A. K. Naji, and R. Ahmad, “Design, synthesis and antitubercular evaluation of novel series of pyrazinecarboxamide metal complexes,” Iran. J. Pharm. Res., vol. 17, no. 1, pp. 93–99, 2018. doi: 10.22037/ijpr.2018.2124.[28]    B. Kozlevčar, B. Zupančič, M. Hren, and B. Šket, "Complexes of copper (II) acetate with nicotinamide: preparation, characterization and fungicidal activity; crystal structures of [Cu2(O2CCH3)4(nia)] and [Cu2(O2CCH3)4(nia)2]," Polyhedron, vol. 18, no. 5, pp. 755-762, 1999. doi: 10.1016/S0277-5387(98)00354-7.[29] O. Kristiansson, “Bis(pyrazine-2-carboxamide)bis(trifluoromethanesulfonato)copper(II) monohydrate,” Acta Crystallogr. Sect. E Struct. Reports Online, vol. 58, no. 3, pp. m130–m132, 2002. doi: 10.1107/S1600536802006196.[30]    N. C. Handayani, I. K. Dewi, M. Surya, and S. Utami, “Synthesis, Characterization, and Antibacterial Activity of Anion-Depended Cu (II)-Niacinamide Complexes,” The Indonesian Green Technology Journal, vol. 11, no. 2, pp. 1–12, 2020.[31]    P. Ghanghas, S. K. Ghanghas, and A. S. Thakur, “Coordination metal complexes with Schiff bases: Useful pharmacophores with comprehensive biological applications,” Inorg. Chem. Commun., vol. 130, p. 108710, 2021. doi: 10.1016/j.inoche.2021.108710.[32]    N. C. S. Mykytczuk, P. L. Trevors, and E. B. Twiss, “Fluorescence polarization in studies of bacterial cytoplasmic membrane fluidity under environmental stress,” Prog. Biophys. Mol. Biol., vol. 95, no. 1–3, pp. 60–82, 2007. doi: 10.1016/j.pbiomolbio.2007.03.001.[33]    S. Njobdi, N. T. J. Jebin, and A. J. Ishaku, “Antibacterial Activity of Zingiber officinale on Escherichia coli and Staphylococcus aureus,” J. Adv. Biol. Biotechnol., vol. 19, no. 1, pp. 1–8, 2018. doi: 10.9734/jabb/2018/39840.[34]    G. Kumaravel, R. R. Mounika, S. Harini, and K. K. Nithya, “Bioorganic Chemistry Exploiting the biological efficacy of benzimidazole based Schiff base complexes with L-Histidine as a co-ligand: Combined molecular docking, DNA interaction, antimicrobial and cytotoxic studies,” Bioorg. Chem., vol. 77, pp. 269–279, 2018. doi: 10.1016/j.bioorg.2018.01.022.[35]    M. Shen, L. Li, T. Hu, and J. Fang, “Antibacterial applications of metal–organic frameworks and their composites,” Compr. Rev. Food Sci. Food Saf., vol. 19, no. 4, pp. 1397–1419, 2020. doi: 10.1111/1541-4337.12558.